Towards brain-tissue-like biomaterials - Eneko Axpe (Nature Portfolio, 2020)
Many biomaterials have been developed which aim to match the elastic modulus of the brain for improved interfacing. However, other properties such as ultimate toughness, tensile strength, poroviscoelastic responses, energy dissipation, conductivity, and mass diffusivity also need to be considered.